Perception of affordances in soccer: Kicking for power versus kicking for precision - Peker, A. T.; Böge, V.; Bailey, G.; Wagman, J. B.; Stoffregen, T. (Research Quarterly for Exercise and Sport, 2022)
Purpose: We investigated youth soccer players` perception of affordances for different types of kicks.